The Effect of Emotional Intelligence on Qur'an Memorization Ability in Islamic Boarding Schools - Arqam, M. Rukhul; Tang, Muhammad; Kamaruddin, Kamaruddin; Indri Karadona, Rosika (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to examine the influence of emotional intelligence on the ability to memorize the Qur'an in students at the Darul Aman Gombara Islamic Boarding School in Makassar. Based on the results of descriptive analysis and statistical tests, it was found that emotional intelligence has a significant influence on memorization ability. The average emotional intelligence score of 68.7 and memorization ability of 63.1 indicate that although the level of emotional intelligence of students is relatively good, their memorization ability is still below it. The regression analysis yielded a correlation coefficient value (R) of 0.474, indicating a moderate relationship between the two variables, and an R-Square value of 0.225 indicating a contribution of emotional intelligence of 22.5% to memorization ability. In addition, the ANOVA test results showed a significance of 0.000, which means the relationship between emotional intelligence and memorization ability is statistically significant. The calculated F-value of 15.345 also supports the validity of the regression model used. These findings confirm the importance of developing emotional aspects in the tahfidz learning process. Emotional coaching that includes emotional management, self-motivation, and spiritual resilience has been shown to contribute to successful Qur'an memorization. Thus, pesantren are expected not only to focus on the technical aspects of memorization, but also to integrate learning strategies that support the balance between students' cognitive and emotional abilities. This holistic approach is believed to be able to improve the quality of memorization more optimally and sustainably.